Impact of modified frequent-pattern generation on cross-selling - Sarmistha Saha, Ms; G. P. Saradhi Varma, MR (International Journal of Engineering and Technology, 2018)
The banking sector is an integral part of the economy. Hence this sector plays a key role in the well being of the economy. In the modern era, all the banks are being computerized to handle smoothly ample of data. In this regard, they all need data mining techniques to discover patterns for unknown relationship of customer data on daily basis. Frequent â€“ Pattern tree construction is one of the popular method. This paper represents new approach for frequent-pattern tree construction where more than one item has same support count and it is mainly useful for cross-selling of products by the banks.Â Â